COVID-19: a novel menace for the practice of nephrology and how to manage it with minor devastation?. Issue 1 (1st January 2020) - Ulu, Sena; Gungor, Ozkan; Gok Oguz, Ebru; Hasbal, Nuri Baris; Turgut, Didem; Arici, Mustafa
Abstract: Coronavirus disease 19 (COVID-19) became a nightmare for the world since December 2019. Although the disease affects people at any age; elderly patients and those with comorbidities were more affected. Everyday nephrologists see patients with hypertension, chronic kidney disease, maintenance dialysis treatment or kidney transplant who are also high-risk groups for the COVID-19. Beyond that, COVID-19 or severe acute respiratory syndrome (SARS) due to infection may directly affect kidney functions. This broad spectrum of COVID-19 influence on kidney patients and kidney functions obviously necessitate an up to date management policy for nephrological care. This review overviews and purifies recently published literature in a question to answer format for the practicing nephrologists that will often encounter COVID-19 and kidney related cases during the pandemic times.